2017
DOI: 10.1073/pnas.1620212114
|View full text |Cite
|
Sign up to set email alerts
|

BGP-15 prevents the death of neurons in a mouse model of familial dysautonomia

Abstract: Hereditary sensory and autonomic neuropathy type III, or familial dysautonomia [FD; Online Mendelian Inheritance in Man (OMIM) 223900], affects the development and long-term viability of neurons in the peripheral nervous system (PNS) and retina. FD is caused by a point mutation in the gene IKBKAP/ELP1 that results in a tissue-specific reduction of the IKAP/ELP1 protein, a subunit of the Elongator complex. Hallmarks of the disease include vasomotor and cardiovascular instability and diminished pain and temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 62 publications
(129 reference statements)
5
38
0
2
Order By: Relevance
“…Our recent study revealed that mitochondria of embryonic Ikbkap CKO dorsal root ganglia neurons are depolarized, produce elevated levels of reactive oxygen species (ROS), are fragmented, and do not aggregate normally at axonal branch points ( Ohlen et al, 2017 ). In support of a mitochondrial deficit in FD, FD patients have a temporal optic nerve degeneration that is reminiscent of LHON and DOA, both of which are caused by mutations that affect mitochondrial function ( Carelli et al, 2009 ; Chevrollier et al, 2008 ; Kirches, 2011 ; Newman and Biousse, 2004 ; Yu-Wai-Man et al, 2011 ; Zanna et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent study revealed that mitochondria of embryonic Ikbkap CKO dorsal root ganglia neurons are depolarized, produce elevated levels of reactive oxygen species (ROS), are fragmented, and do not aggregate normally at axonal branch points ( Ohlen et al, 2017 ). In support of a mitochondrial deficit in FD, FD patients have a temporal optic nerve degeneration that is reminiscent of LHON and DOA, both of which are caused by mutations that affect mitochondrial function ( Carelli et al, 2009 ; Chevrollier et al, 2008 ; Kirches, 2011 ; Newman and Biousse, 2004 ; Yu-Wai-Man et al, 2011 ; Zanna et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we demonstrated that mitochondria of Ikbkap CKO embryonic PNS neurons were fragmented, had disrupted membrane potential and had increased ROS ( Ohlen et al, 2017 ). In this new study, we show that mitochondria of Ikbkap -deficient retinal neurons are also morphologically and functionally impaired ( Figs 4 - 6 ), demonstrating that mitochondrial dysfunction occurs in both developing and adult neurons in the PNS and CNS in the absence of IKAP.…”
Section: Discussionmentioning
confidence: 99%
“…FD patients also suffer frequently from rhabdomyolysis, which can result from mitochondrial-induced myopathy [59]. These findings provoked a detailed investigation of mitochondrial function in DRG neurons from Wnt1-cre;Ikbkap LoxP/LoxP mice [60], which revealed that mitochondria in Ikbkap depleted DRG neurons were depolarized, fragmented and released elevated levels of reactive oxygen species (ROS) compared to their control littermate DRG neurons. Furthermore, this study also showed that the small hydroxylamine, BGP-15 which has been shown in numerous studies to be cytoprotective by exerting anti-oxidative damage effects, could not only significantly improve mitochondrial function in the CKO neurons, but could also prevent their death both in vitro and in vivo [60].…”
Section: Mouse Models Of Familial Dysautonomiamentioning
confidence: 99%
“…These findings provoked a detailed investigation of mitochondrial function in DRG neurons from Wnt1-cre;Ikbkap LoxP/LoxP mice [60], which revealed that mitochondria in Ikbkap depleted DRG neurons were depolarized, fragmented and released elevated levels of reactive oxygen species (ROS) compared to their control littermate DRG neurons. Furthermore, this study also showed that the small hydroxylamine, BGP-15 which has been shown in numerous studies to be cytoprotective by exerting anti-oxidative damage effects, could not only significantly improve mitochondrial function in the CKO neurons, but could also prevent their death both in vitro and in vivo [60]. These findings and those from several other of the studies described here demonstrate not only the power of mouse models to provide the necessary cell types for elucidation of the pathophysiological mechanisms that cause the FD phenotype, but also their effectiveness as a readily accessible and defined system for testing potential therapeutics.…”
Section: Mouse Models Of Familial Dysautonomiamentioning
confidence: 99%
“…[156][157][158] Furthermore, by studying the cell biology of developing neurons in FD mouse models, it has become clear that in the absence of Elp1, neurons undergo intracellular stress, marked by elevated p53, increased pJNK, depolarized mitochondria, increased levels of reactive oxygen species, and impaired mitochondrial function. 152,159 Rett Syndrome…”
Section: Familial Dysautonomiamentioning
confidence: 99%